Analysis of Student Interest in Continuing Economics Education at FKIP Untan Among Accounting Students - Panjaitan, Jesica Sesilia Anggita; Okianna, Okianna; Budiman, Jumardi (Universitas Tanjungpura, 2025)
This study aims to describe the interest of eleventh-grade Accounting students at SMKN 3 Pontianak in continuing their education to the Economics Education Study Program at the Faculty of Teacher Training and Education (FKIP), Tanjungpura University, and to identify supporting and inhibiting factors influencing such interest. The research employed a quantitative approach with a survey method. A total sample of 105 students was randomly selected from the overall population of 141 students. Data were collected using a Likert-scale questionnaire consisting of seven indicators of interest: enjoyment, desire, attention, need, expectation, encouragement, and willingness. The findings revealed that students’ interest in pursuing higher education in the Economics Education Study Program remains relatively low, with only 5.7% categorized as very high, 9.5% high, 19% moderate, 48.6% low, and 17.1% very low. Supporting factors included curiosity and external influences such as teachers and alumni, which were generally rated high to very high. In contrast, inhibiting factors such as attention, motivation, needs, enthusiasm, emotions, family upbringing, economic conditions, and peer influence were predominantly rated low to very low. These results are expected to provide valuable input for schools, parents, and universities to develop strategies that can foster students’ interest in continuing their education, particularly in the Economics Education Study Program at FKIP Tanjungpura University.